Parental aspirations for children’s early childhood education enrolment in Bangladesh - Md Jahangir Alam; Keiichi Ogawa (Institute of Advanced Engineering and Science, 2023)
Early childhood education (ECE) contributes to all young children’s cognitive and non-cognitive development. Most developed countries invest in early childhood education to boost human capital development. In countries such as Bangladesh which are impoverished and underdeveloped, the government has not provided enough access, enrollment, and quality early childhood education. Consequently, parents motivate early childhood education, whose financial circumstances alter to enroll children in school. This study examines the parental aspiration that encourages and motivates them to enroll their children in ECE schools. FGDs and KIIs were conducted with the individual respondents using a qualitative case study method. The findings indicate that parental aspirations, anxieties, and socio-economic conditions significantly affect children’s enrollment in ECE schools. The probability that a child will be enrolled in an ECE school is heavily influenced by the socio-economic position of parents, social recognition, quality of service, and the school’s reputation. This study argued that parental aspiration for children’s enrollment and non-enrollment in ECE impede social justice in education for all children. Finally, all the stakeholders should take innovative policy initiatives to ensure institutional justice and equal enrollment opportunities for children aged 3-5.